Comunicação alternativa para crianças com paralisia cerebral não verbais : programa de intervenção para contextos de vida diária - Manzini, Mariana Gurian (Universidade Federal de São Carlos, 2017)
Introduction: Children with complex communication needs benefit from rehabilitation programs directed to the orientation and instrumentalization of the user, the family and the school. Objective: To elaborate, implement and analyze the effectiveness of an individualized alternative communication program for children with nonverbal cerebral palsy applied together in three of their daily life contexts: school, residential and clinical. Method: The participants were: 03 children diagnosed with cerebral palsy with their respective interlocutors from the contexts already mentioned: teachers, family members and therapists. The research was carried out at the children's school, at the residence of the participants and at an outpatient school unit linked to a university. To reach the objectives of the research was the design of multiple probes by situations (clinical, home and school) involving 2 phases probing and intervention. The instruments for data collection used were: Protocol of characterization of the participants, Interview script with the interlocutors on the communicative abilities of the child, Protocol for selection of the figures, Road map to analyze the perception of the interlocutors on the implementation of the supplementary communication and / or alternative and Questionnaire of social validity. The data collection and analysis were structured in 5 phases: Phase 1 Initial Survey: Knowledge of the characteristics of the participants and the initial repertoire, Phase 2, 3, 4 Intervention: Theoretical, practical training and preparation of the alternative communication resource and Phase 5 Final Score: Final Score of the acquired skills. Results: The results demonstrated: (1) demand for improvements in the communication of the interlocutors (of the 3 contexts) for failing to recognize the needs and desires of the children needing alternative resources to make this communication meaningful and effective; (2) lack of repertoire of participants' input in relation to alternative communication; (3) that the Multiple Probe Design allowed to carry out a planned intervention, in order to guarantee control of the variables; (4) acquisition of new communicative skills by the children and (5) that from the instrumentalization of the participants the act of "changing a pictographic figure by its corresponding object" took place, which made it possible for the child and the interlocutors to use the alternative communication features with independence, functionality and low level of help. Conclusion: The implementation of an individualized alternative communication program aimed at the interlocutors of children with nonverbal cerebral palsy in three of their development contexts favored the increase of the communicative abilities of these children and promoted changes in the behavior of children in the three contexts (school, clinic and house). Through the results, the research revealed that the Alternative Communication Program was effective in the intervention strategies adopted.
Keywords: Comunicação alternativa; Contextos de vida diária; Habilidades comunicativas; Alternative communication; Contexts of daily life; Communicative skills; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO